Sensorimotor rhythm and muscle activity in patients with stroke using mobile serious games to assist upper extremity rehabilitation - Chen, Zihe; Yan, Tingmin; Wu, Jinchun; Liu, Yixuan; Zhang, Chunyun; Cui, Tianjian (Frontiers in Rehabilitation Sciences, 2023)
Exercise rehabilitation is crucial for neurological recovery from upper limb (UL) dysfunction caused by hemiplegia. Previous studies have demonstrated that technology-assisted activation of cortical tissue in the sensorimotor areas of the brain can restore impaired motor function in patients. This study aimed to explore the feasibility of playing mobile serious games for the rehabilitation of motor function in patients with stroke. In this study, we developed a serious gaming mobile application using rehabilitation games for shoulder, elbow, and wrist training. Twelve stroke survivors with varying degrees of motor impairment in subacute or chronic phase attempted the same motor task under two different conditions: serious mobile game-assisted rehabilitation and conventional rehabilitation. We evaluated the effects of the rehabilitation therapy using electroencephalography and electromyography. In addition, as the motor task was attempted, event-related desynchronization (ERD) and root mean square (RMS) were measured, and the results were compared. The comparison showed that the motor perception areas of the contralateral hemisphere of patients with hemiplegia had stronger ERD after game-assisted rehabilitation than after conventional rehabilitation (P<0.05). Furthermore, the RMS during game-assisted rehabilitation was greater than that during conventional rehabilitation; however, the increase was statistically significant (P<0.05) only in shoulder training. Our results indicate that rehabilitation assisted with serious mobile games may play a role in activating the motor cortex of the patient's brain but does not directly improve muscle activity.